2012
DOI: 10.1021/bi300909q
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Effects of Macromolecular Crowding on Protein Stability

Abstract: Most theories about macromolecular crowding focus on two ideas: the macromolecular nature of the crowder and entropy. For proteins, the volume excluded by the crowder favors compact native states over expanded denatured states, enhancing protein stability by decreasing the entropy of unfolding. We tested these ideas with the widely used crowding agent Ficoll-70 and its monomer, sucrose. Contrary to expectations, Ficoll and sucrose have approximately the same stabilizing effect on chymotrypsin inhibitor 2. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
221
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 201 publications
(234 citation statements)
references
References 42 publications
13
221
0
Order By: Relevance
“…1 A and B predicts a generic "baseline" stabilization of all folded protein states, all higher oligomer states, and all ligand-protein bound states, whereas the evidence suggests very variable degrees of effect. Second, size effects should be purely entropic, whereas enthalpic contributions are often seen (6,7). Third, crucially, in an earlier study Pielak and coworkers (6) did not find the dependence on crowding molecule size predicted by the conventional model of Fig.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…1 A and B predicts a generic "baseline" stabilization of all folded protein states, all higher oligomer states, and all ligand-protein bound states, whereas the evidence suggests very variable degrees of effect. Second, size effects should be purely entropic, whereas enthalpic contributions are often seen (6,7). Third, crucially, in an earlier study Pielak and coworkers (6) did not find the dependence on crowding molecule size predicted by the conventional model of Fig.…”
mentioning
confidence: 88%
“…Second, size effects should be purely entropic, whereas enthalpic contributions are often seen (6,7). Third, crucially, in an earlier study Pielak and coworkers (6) did not find the dependence on crowding molecule size predicted by the conventional model of Fig. 1 A and B. Here they examine the size dependence in more detail by comparing the effect on SH3 stability of the neutral polymers dextran, Ficoll, and PEG vs. their corresponding monomers glucose, sucrose, and ethylene glycol, respectively: chemically identical pairs of molecules of vastly different size.…”
mentioning
confidence: 99%
“…That is, an increased ΔG den o' was not always associated with a decreased ΔS den o' (and vice versa), plus the change in ΔH den o' was non-zero. As pointed out by Benton et al (2012), some of the complication observed for synthetic polymers may arise from the influence of preferential hydration (Timasheff 1993). In summary, the simplest ideas about macromolecular crowding predict entropically derived stabilization, but recent studies indicate that attractive, non-specific interactions complicate this interpretation.…”
Section: Enthalpy and Entropymentioning
confidence: 99%
“…This phenomenon has been studied theoretically and experimentally. Theoretical models have been successful in mimicking the hard-core repulsion effect (e.g., Berg 1990;Rivas et al 2001;Zhou et al 2008;McGuffee and Elcock 2010), and many 'wet' experiments show that crowding by synthetic polymers stabilizes proteins (e.g., Sasahara et al 2003;Stagg et al 2007;Charlton et al 2008;Christiansen et al 2010;Miklos et al 2010;Benton et al 2012). These observations are consistent with theoretical expectations in as much as the stabilizing hard-core repulsions seem to dominate, although significant attractive protein-crowder interactions have been noted for polyethylene glycol (Crowley et al 2008;Hirota et al 2010;Zhang et al 2012) and the monomer of polyvinylpyrrolidone .…”
Section: Crowding and Assemblymentioning
confidence: 99%
See 1 more Smart Citation